Study on myrmecodia platytyrea antoinii tuber and its potential benefits in preventing hypercholesterolemia related diseases / Mohd Kamal Nik Hasan - Nik Hasan, Mohd Kamal (Institute of Graduate Studies, UiTM, 2018)
This study was designed in order to investigate the effect of Myrmecodia platytyrea (MyP) extract as an anti-hypercholesterolemic agent. The acute toxicological test was done by administration of single dose and followed by 14 days observation on the rat. The subchronic toxicological test was done by administration of 28 days repeated dose. Both tests showed that MyP water extract was not toxic. The bioassay-guided isolation revealed that the MyP water extract containing 2-(2-methylbutyryl) phloroglucinol glucoside which reduced 3-hydroxy-3-methylglutaryl-CoA reductase (HMGR) activity (p<0.05) with inhibition concentration 50 (IC₅₀) of 75 μg/ml. Besides that, polysaccharide showed effective concentration 50 (EC₅₀) of 50.5 μg/ml for bile acid binding. Meanwhile, rutin actively decreased pancreatic lipase activity with IC₅₀ of 130 μg/ml. Moreover, in vivo study results showed that treatment of MyP water extract can significantly reduce (p<0.05) low-density lipoprotein (LDL) compared to negative control group. The extract significantly increased (p<0.05) high-density lipoproteins (HDL) concentration compared to negative control group. In addition, MyP water extract increased faecal cholesterol and faecal bile compared to normal control group. Lipid peroxidation was significantly decreased (p<0.05) in MyP water extract treatment group. The extract also decreased the formation of the fatty streak at the aorta and significantly decreased (p<0.05) the thickness of foam cell in high cholesterol diet (HCD) induced rat…